2020
DOI: 10.5194/hess-2020-404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating the impacts of biochar on water fluxes in tropical agriculture using stable isotopes

Abstract: Abstract. Amending soils with biochar, a pyrolyzed organic material, is an emerging practice to potentially increase plant available water. However, it is not clear (1) to what extent biochar amendments increase soil water storage relative to non-amended soils and (2) whether plants grown in biochar amended soils access different pools of water compared to those grown in non-amended soils. To investigate these questions, we set up an upland rice field experiment in a tropical seasonally dry region in Costa Ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…The shallower the measurement location, the stronger the influence from atmospheric forcing and consequently the larger the fluctuations of the measurements, explaining the higher variability of the in situ measurements compared to the remote sensing estimates. Besides, the groundwater level was reported 0.8 m below the surface during the dry period [25] and the capillary rise in clay loam soil of the site might dampen the fluctuations of root zone soil moisture. The mismatch of in situ sensor-measured and UAV-derived  makes the two sets of data not readily comparable.…”
Section: Biochar Effects On Soil Water Availabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…The shallower the measurement location, the stronger the influence from atmospheric forcing and consequently the larger the fluctuations of the measurements, explaining the higher variability of the in situ measurements compared to the remote sensing estimates. Besides, the groundwater level was reported 0.8 m below the surface during the dry period [25] and the capillary rise in clay loam soil of the site might dampen the fluctuations of root zone soil moisture. The mismatch of in situ sensor-measured and UAV-derived  makes the two sets of data not readily comparable.…”
Section: Biochar Effects On Soil Water Availabilitymentioning
confidence: 99%
“…Harvest took place on 21 November 2018 and indicated the end of the experiment. See [25] for details of biochar experimental design. Figure 1.…”
Section: Biochar Experiments Plotsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these findings, the authors hypothesized that amending biochar into the top 10-30 cm of the soil, could increase soil water storage and rice plants be able to use water from different soil water pools in comparison to plants grown in non-amended soils (L113-125) across the different time periods studied. First, I should say that after the work of Brooks et al (2020), countless studies across regions (including tropical wet environments; see Goldsmith et al 2012;Muñoz-Villers et al 2018) and revisions have showed that plants use evaporatively fractionated soil water (Sprenger et al, 2016;Sprenger and Allen 2020). The general finding is that plant water is isotopically similar to bulk soil water but not to low suctionâȂŘlysimeter water, implying that roots are generally located in less conductive (mobile) pores where water tends to travel more slowly and can reside for longer times.…”
mentioning
confidence: 99%